Effectiveness of Core Stability Exercise and Proprioception Exercise on Balance in Subjects with Diabetic Neuropathy- A Randomized Controlled Trial. - Pavana; Premrajan, Nair Anjali; Ghosh, Amrita (Indian Journal of Physiotherapy & Occupational Therapy)
Background and Objectives: Long standing Diabetes Mellitus leads to Diabetic Peripheral Neuropathy in the subjects which alter their daily activities performed. As physical activities are the key elements to prevent the further progress of Diabetes Mellitus. The neuropathy also affects the postural stability leading to impaired balance and risk of falls in the subjects. The integrated activity of the motor and the sensory systems play an important role in maintain the postural stability which depends upon the strength of the core muscles and proper integrated activity of the proprioceptors of the lower limb. The prevalence of the Diabetic Peripheral neuropathy in India is around 10.5% to 32.2%. The Toronto Clinical scoring System is used as a marker to assess the level of neuropathy which has a relation on the stability. Thus, the aim of the study is to find the effectiveness of proprioception exercise or core stability exercise on balance in Diabetic Peripheral Neuropathy subjects. Objectives: To assess the effectiveness of core stability exercise on balance in Diabetic Neuropathy subjects. To assess the effectiveness of proprioception exercise on balance in Diabetic Neuropathy subjects. To compare the effectiveness of core stability exercise and proprioceptive exercise on balance in Diabetic Neuropathy subjects. Design: Comparative Randomized Parallel Open Label Study Methods: Eighty subjects between the age 40-60 years were recruited for the study. Written informed consent and institutional ethical clearance was obtained. Demographic data were obtained and subjects were assigned to one of two groups: Group A: experimental group given Proprioception exercise (n=40) and Group B: control group given Core Stability exercise (n=40). The therapy was given for six weeks with three days in a week and was measured with Berg Balance Scale as an outcome measure at the end of the 6 week protocol. Results: Both the groups showed improvement in the balance according to the Berg Balance Scale. The mean ± SD of pre and post Berg Balance Scale of GROUP A was 37.18 ± 4.81 and 39.41 ± 4.95 respectively and that of GROUP B was 36.95 ± 4.27 and 38.55 ± 4.29 respectively. Conclusion: The results showed a significant improvement within Group A and Group B (P<0.001) but there is no significant improvement between both the groups (P>0.05). Thus the study concluded that proprioception exercise and core stability exercise are worthwhile in improving the balance in subjects with diabetic peripheral neuropathy.